Social Media, Selfie Culture and Art Museums: Shifting Behavior in Art Museum Visitors - ., Hariyanto (KnE Social Sciences, 2020)
Smartphone users have a new habit of taking selfies then posting to Instagram or Facebook which will then be liked and commented on by their friends. This selfie culture influences the visitors of fine arts exhibitions and museums driving the urge to take a selfie in front of the work on display. Taking a selfie in front of a work of art seems to show the self-expression and self-identity of the performer. Selfie photos have similarities with self-portrait paintings by famous painters from the Reneisance era to the present. Selfie culture has influenced the behavior of millennials in appreciating works of art. Some applications that support selfie culture have been developed and gives smartphone users the opportunity to use it to create new interpretations of images. This article discusses the shift in exhibit behavior at the fine arts museum which is shown through photos uploaded on social media. Keywords: social media, selfies, art museum